A Comprehensive Review of Theories in Supply Chain Management - Lawal Abideen Ayokunmi; Abu Seman, Noor Aslinda; Umi Kartini Rashid (JBS Nexus, 2024)
This paper explores various theoretical perspectives in supply chain management (SCM) and aims to identify key topics within the field while suggesting areas for future development. Through a literature review, it seeks to map out the use of theories within SCM research, analyzing related themes and examining commonly referenced theories. The paper highlights the scarcity of theory-building efforts in SCM, with the dominance of a few widely adopted macro theories influencing how SCM has been conceptualized and studied. Further theoretical contributions can emerge by applying specific methodologies, investigating less-explored aspects of SCM, and testing recently developed frameworks. Based on this review, an overarching map of prominent SCM theories is presented, along with potential pathways for advancing the field. Several recommendations are offered to guide future research, providing an initial step toward understanding how SCM theories are evolving and how the field has been conceptualized.